COVID-19 in Patients with Hematologic Diseases - Ilaria Carola Casetti; Oscar Borsani; Elisa Rumi (Biomedicines, 2022)
The COVID-19 outbreak had a strong impact on people’s lives all over the world. Patients with hematologic diseases have been heavily affected by the pandemic, because their immune system may be compromised due to anti-cancer or immunosuppressive therapies and because diagnosis and treatment of their baseline conditions were delayed during lockdowns. Hematologic malignancies emerged very soon as risk factors for severe COVID-19 infection, increasing the mortality rate. SARS-CoV2 can also induce or exacerbate immune-mediated cytopenias, such as autoimmune hemolytic anemias, complement-mediated anemias, and immune thrombocytopenia. Active immunization with vaccines has been shown to be the best prophylaxis of severe COVID-19 in hematologic patients. However, the immune response to vaccines may be significantly impaired, especially in those receiving anti-CD20 monoclonal antibodies or immunosuppressive agents. Recently, antiviral drugs and monoclonal antibodies have become available for pre-exposure and post-exposure prevention of severe COVID-19. As adverse events after vaccines are extremely rare, the cost–benefit ratio is largely in favor of vaccination, even in patients who might be non-responders; in the hematological setting, all patients should be considered at high risk of developing complications due to SARS-CoV2 infection and should be offered all the therapies aimed to prevent them.